A short term evaluation of effect on serum urea, creatinine and potassium levels with use of angiotensin II receptor blockers (olmesartan or telmisartan) in stage 1 hypertensive patients - Gupta, Varun; Singh, Pooja (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers (ARBs) are being used as first line agents for the treatment of hypertension in haemodialysis patients as well as in the general population. Serious hyperkalemia is common in patients with end-stage renal disease, and is observed in about 10% of haemodialysis patients. Although many research have been done so far to compare the antihypertensive efficacy of ARBs, but such studies to evaluate the effect on serum urea, creatinine and potassium levels are not so common in North India region. Methods: In this open label, prospective, randomized study, we evaluated the effect on serum urea, creatinine and potassium levels with use of ARB’s (olmesartan or telmisartan) in stage 1 hypertensive patients (JNCVII). 60 patients were randomized in to two groups. The odd numbers will be allotted olmesartan 20 mg (group A) and even numbers to telmisartan 40 mg (group B). Impacts on serum urea, creatinine and potassium levels were evaluated after 12 weeks. Results: Our results indicates that there was no statistically significant alterations in mean serum creatinine, blood urea and in mean serum potassium levels compared to baseline within the two groups as well as when mean of both groups were compared, olmesartan showed a better reduction in blood pressure as compared to telmisartan. Conclusions: Olmesartan showed a better reduction in blood pressure with similar effects in biochemical parameters as telmisartan.